Recherches sur la collection d’enfants et d’adolescents d’âge et de sexe connus de Bologne (Italie) : diagnose de l’âge sur la base du degré de maturation osseuse - Silvia Veschi; Fiorenzo Facchini (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The purpose of this study is the assessment of age at death in immature human skeletons through observation of the degree of skeletal maturation, in particular the appearance of ossification centres and their successive fusion. Most of the methods employed are based on studies of living children or on American skeletal collections. Our aim was to shed light on the assessment of skeletal age maturation on European populations by analysing two samples from the Bologna collection dated to the beginning of the 20th c. AD. The skeletons analysed are those of immature individuals of known age and sex; 137 were children (0 to 8 years) from Bologna, and 131 were juvenile (15-25 years) from Sardinia.